THE SHELL ACTIVITY OF Be/SHELL STAR ζ TAURI IN 1985 - 1997 - Pan'ko, E. A. (Одеські астрономічні публікації, 2017)
The study results of highresolution CCD-spectra of the V/R variable Be-shell star ζ Tauri covering 1985 - 1997 obtained at the 2.6-m telescope of the Crimean Astrophysical Observatory are present. The equivalent width, the violet and red intensities and V/R ratio of the Hα emission line and equivalent width and central depth of the HeII 6678 line were measured. The shell activity was low in 1985-1988: the equivalent width Hog emission line were about 7-12 Å V/R ratio fluctuated in an irregular manner. The active shell phase started in 1989 and then equivalent width of Hα emission line increased to 19-26 Å in 1992 - 1995; V/R cyclic changes and compound structure of Hα emission line profiles reappeared. In 1996 - 1997 the equivalent wight of Hα line slightly lessened, but compound profiles structure remained.